Normal structural brain development in adolescents treated for perinatally acquired HIV: a longitudinal imaging study. (1st July 2021) - Van den Hof, Malon; Jellema, Pien E.J.; ter Haar, Anne Marleen; Scherpbier, Henriette J.; Schrantee, Anouk; Kaiser, Antonia; Caan, Matthan W.A.; Majoie, Charles B.L.M.; Reiss, Peter; Wit, Ferdinand W.N.M.; Mutsaerts, Henk-Jan M.M.; Pajkrt, Dasja
Abstract : Objective: Cross-sectional studies, including one from our NOVICE cohort [Neurological Visual and Cognitive performance in children with treated perinatally acquired HIV (PHIV) compared with matched HIV-negative controls], have revealed that the brains of children with PHIV have lower white matter and grey matter volumes, more white matter hyperintensities (WMH) and poorer white matter integrity. This longitudinal study investigates whether these differences change over time. Methods: We approached all NOVICE participants to repeat MRI after 4.6 ± 0.3 years, measuring total white matter and grey matter volume, WMH volume and white matter integrity, obtained by T1-weighted, fluid-attenuated inversion recovery (FLAIR) and diffusion tensor imaging (DTI), respectively. We compared rates of change between groups using multivariable linear mixed effects models, adjusted for sex and age at enrolment. We investigated determinants of developmental deviation, and explored associations with cognitive development. Results: Twenty out of 31 (65%) PHIV-positive, and 20 out of 37 (54%) HIV-negative participants underwent follow-up MRI. Groups did not significantly differ in terms of age and sex. Over time, we found no statistically different changes between groups for white matter and WMH volumes, and for white matter integrity ( P  > 0.1). Total grey matter volume decreased significantly less in PHIV [group*time 10 ml, 95% confidence interval −1 to 20, P  = 0.078], but this difference in rate of change lost statistical significance after additional adjustment for height (group*time 9 ml, 95% confidence interval −2 to 20, P  = 0.112). We found no HIV-associated determinants for potential reduced grey matter pruning, nor associations with cognitive development. Conclusion: While using long-term antiretroviral treatment, structural brain development of adolescents growing up with perinatally acquired HIV appears largely normal. Abstract : Supplemental Digital Content is available in the text